Polypeptide and Protein Modeling for Drug Design - O'Mara, M.; Deplazes, Evelyne (2014)
The main pathways involved in pain processing have been known for some time, but the precise microcircuitry remains surprisingly unclear. This has allowed very different theories of pain processing to persist. Specificity theory holds that pain is qualitatively distinct from other somatosensory percepts and that the underlying circuitry is arranged as labeled lines. Gate control theory holds that all inputs converge and that it is the level of activation in unspecialized neurons that code for pain. The truth lies somewhere in between. The dorsal horn of the spinal cord, which corresponds to the first synaptic relay point, comprises a diverse set of interneurons whose connectivity is only partially worked out. This lack of data has hindered network-level modeling, but this also presents an opportunity for modeling to help guide future experiments.